Separating fast and slow exchange transfer and magnetization transfer using off‐resonance variable‐delay multiple‐pulse (VDMP) MRI. Issue 4 (5th February 2018) - Chen, Lin; Xu, Xiang; Zeng, Haifeng; Chan, Kannie W.Y.; Yadav, Nirbhay; Cai, Shuhui; Schunke, Kathryn J.; Faraday, Nauder; van Zijl, Peter C.M.; Xu, Jiadi
Abstract : Purpose: To develop a method that can separate and quantify the fast (>1 kHz) and slow exchange transfer and magnetization transfer components in Z‐spectra. Methods: Z‐spectra were recorded as a function of mixing time using a train of selective pulses providing variable‐delay multipulse build‐up curves. Fast and slow transfer components in the Z‐spectra were separated and quantified on a voxel‐by‐voxel basis by fitting the mixing time–dependent CEST signal using a 3‐pool model. Results: Phantom studies of glutamate solution, bovine serum albumin solution, and hair conditioner showed the capability of the proposed method to separate fast and slow transfer components. In vivo mouse brain studies showed a strong contrast between white matter and gray matter in the slow‐transferring map, corresponding to an asymmetric component of the conventional semisolid magnetization transfer contrast. In addition, a fast‐transferring proton map was found that was homogeneous across the brain and attributed to the total contributions of the fast‐exchanging protons from proteins, metabolites, and a symmetric magnetization transfer contrast component. Conclusions: This new method provides a simple way to extract fast and slow transfer components from the Z‐spectrum, leading to novel MRI contrasts, and providing insight into the different magnetization transfer contrast contributions.